The role of the anterior, mediodorsal, and parafascicular thalamus in instrumental conditioning - Bradfield, Laura A.; Hart, Genevra; Balleine, Bernard W. (Frontiers in Systems Neuroscience, 2013)
The traditional animal model of instrumental behaviour has focused almost exclusively on structures within the cortico-striatal network and ignored the contributions of various thalamic nuclei despite large and specific connections with each of these structures. One possible reason for this is that the thalamus has been conventionally viewed as a mediator of general processes, such as attention, arousal and movement, that are not easily separated from more cognitive aspects of instrumental behaviour. Recent research has, however, begun to separate these roles. Here we review the role of three thalamic nuclei in instrumental conditioning: the anterior, the mediodorsal, and parafascicular thalamic nuclei. Early research suggested that anterior thalamic nuclei might regulate aspects of instrumental behaviour but, on review, we suggest that the types of tasks used in these studies were more likely to recruit Pavlovian processes. Indeed lesions of anterior thalamic nuclei have been found to have no effect on performance in instrumental free-operant tasks. By contrast the mediodorsal thalamus has been found to play a specific and important role in the acquisition of goal-directed action. We propose this role is related to its connections with prelimbic cortex and present new data that directly implicates this circuit in the acquisition of goal-directed actions. Finally we review evidence suggesting the parafascicular thalamic nucleus, although not critical for the acquisition or performance of instrumental actions, plays a specific role in regulating action flexibility.